Presence of virulence factors and antibiotic resistance among Escherichia coli strains isolated from human pit sludge - Mahmud, Zahid Hayat; Shirazi, Farozaan Fatima; Hossainey, Muhammad Riadul Haque; Islam, Mohammad Imtiazul; Ahmed, Mir Alvee; Nafiz, Tanvir Noor; Imran, Khan Mohammad; Sultana, Jinath; Islam, Md Shafiqul; Islam, Mohammad Aminul; Islam, Md Sirajul (The Journal of Infection in Developing Countries, 2019)
Introduction: In Bangladesh, human sludge from dry pit latrines is commonly applied directly to agricultural lands as manure. This study was conducted to investigate the presence of antibiotic resistance, virulence factors and plasmid contents of E. coli strains isolated from sludge samples. Methodology: E. coli were isolated from human feces from closed pit latrines and identified by culture method. Antibiotic susceptibility patterns of the isolates were determined by Standard Kirby-Bauer disk diffusion method. Pathogenic genes and antibiotic resistance genes of ESBL producing isolates were determined by PCR assay. Results: Of the 34 samples tested, 76.5% contained E. coli. Of 72 E. coli isolates, 76.4% were resistant to at least one of the 12 antibiotics tested and 47.2% isolates were resistant to three or four classes of antibiotics. Around 18% isolates were extended spectrum β- lactamase producing and of them 6 were positive for blaTEM specific gene, 4 for blaCTX-M gene, 1 for blaOXA gene and 2 for both blaTEM and blaCTX-M genes. Moreover, among 72 isolates, 4.2% carried virulence genes of enterotoxigenic E. coli; two isolates were positive for st and one was positive for both st and lt genes. In addition, 59.7% of the isolates contained plasmids (range 1.4 to 140 MDa) of which 19.5% isolates contained a single plasmid and 40.2% contained multiple plasmids. Conclusions: The presence of pathogenic, drug resistant E. coli in human sludge necessitates a regular surveillance before using as a biofertilizer.